2009
DOI: 10.1021/ic901078u
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic NMR Study of Ethene Exchange in Cationic CNN-Type Platinum(II) Complexes

Abstract: Cationic ethylene platinum(II) complexes of the type [Pt(CNN)(C(2)H(4))](+), containing a methyl fragment and different diimines (NN), or terdentate (kappaC-kappa(2)NN') anionic ligands, were synthesized and fully characterized both as solids and in solution [NN = 2,2'-dipyridylamine, 1; 2,2'-dipyridylsulfide, 2; 1,10-phenanthroline, 3; 4,7-diphenyl-1,10-phenanthroline, 4; 3,4,7,8-tetramethyl-1,10-phenanthroline, 5; 2,2'-bipyridine, 6; HC-NN = 6-tert-butyl-2,2'-bipyridine, 7; 6-neo-pentyl-2,2'-bipyridine, 8; 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 97 publications
2
9
0
Order By: Relevance
“…A smaller amount of energy is required to displace the B(C 6 F 5 ) 4 À anion from the first coordination sphere but, because of the fact that the degrees of mobility of B(C 6 F 5 ) 4 À are similar in ISIPs and OSIPs, the recovery of entropy is smaller and approaches the typical value of DS°of an associative bimolecular process occurring in low polar solvents (around À50 cal mol À1 K À1 ). [36][37][38][39] Notably, almost the same recovery of entropy (DS°= À44 AE 5 cal mol À1 K À1 ) was observed for the sole olefin polymerization catalyst with the MeB(C 6 F 5 ) 3 À counterion in the second coordination sphere. [29] The insertion of 2 in 1a and 1b is around 3-5 and 50-100 times slower, respectively, in [D 8 ]toluene/[D 5 ]chlorobenzene than in [D 8 ]toluene (DDG°= 0.5-1.0 and 2.2-2.5 kcal mol À1 for 1a and 1b, respectively) and the anion has no effect on the insertion rate (Table 1, entries 9-16).…”
Section: Angewandte Chemiesupporting
confidence: 56%
“…A smaller amount of energy is required to displace the B(C 6 F 5 ) 4 À anion from the first coordination sphere but, because of the fact that the degrees of mobility of B(C 6 F 5 ) 4 À are similar in ISIPs and OSIPs, the recovery of entropy is smaller and approaches the typical value of DS°of an associative bimolecular process occurring in low polar solvents (around À50 cal mol À1 K À1 ). [36][37][38][39] Notably, almost the same recovery of entropy (DS°= À44 AE 5 cal mol À1 K À1 ) was observed for the sole olefin polymerization catalyst with the MeB(C 6 F 5 ) 3 À counterion in the second coordination sphere. [29] The insertion of 2 in 1a and 1b is around 3-5 and 50-100 times slower, respectively, in [D 8 ]toluene/[D 5 ]chlorobenzene than in [D 8 ]toluene (DDG°= 0.5-1.0 and 2.2-2.5 kcal mol À1 for 1a and 1b, respectively) and the anion has no effect on the insertion rate (Table 1, entries 9-16).…”
Section: Angewandte Chemiesupporting
confidence: 56%
“…ΔG q values for related systems ranged from ∼14.5 kcal/mol to <9.5 kcal/mol. 85 We attempted to calculate the energetics of a second insertion of ethylene from [ …”
Section: 61à67mentioning
confidence: 99%
“…As a consequence, only one stereoisomer was observed in the case of α-olefins in the temperature range 203-328 K (actually only one couple of enantiomers), namely I I of Figure 3, in which the steric contacts are minimized by orienting the alkene substituent RЈЈ toward the Pt-Me bond. These qualitative studies were recently [12] confirmed and implemented by preparing other complexes of the same general type (I-38 to I-42), along with related cyclometalated platinum(II) species (I-54 to I-59). These compounds were analogously synthesized by substituting the halides of neutral [PtCl(N,NЈ,C)] precursors with ethylene in the presence of a silver or sodium salt.…”
Section: Arrangement Of An Alkyl Group and An Alkene (I)mentioning
confidence: 75%